Characteristics of ZnO Schottky photodiode and effects of high‐energy proton irradiation. Issue 3 (11th November 2013) - Narita, S.; Endo, H.; Chiba, T.; Sakemi, Y.; Itoh, M.; Yoshida, H.
<x xml:space="preserve">Abstract</x> We fabricated a Pt/ZnO Schottky photodiode based on single‐crystal substrates grown by the hydrothermal growth method. We measured the electrical properties and the spectral responsivity in UV region. The responsivity was 0.1 W/A and there was a sharp cutoff wavelength corresponding to the band gap of ZnO. The fabricated diode can be used as a visible–blind sensor. We also investigated the performance of the diode for the incidence of X‐rays and observed the signal obtained. We demonstrated the potential of the ZnO device for ionizing radiation.In addition, we investigated the effects of irradiating the photodiode with high energy protons. For a sample irradiated with ∼1015 protons/cm2, the dark currents were observed to increase by a factor of 10. Moreover, the behavior of the forward currents significantly changed. In the current–voltage measurement 2 months after irradiation, the dark current decreased to the same level as that before irradiation. This behavior of the dark current may indicate that the defects generated by proton irradiation had been annihilated.